Assessment of Calanus finmarchicus growth and dormancy using the aminoacyl-tRNA synthetases method - Yebra, Lidia; Hirst, A.G.; Hernández León, Santiago (Journal of Plankton Research, 2006)
We obtained growth rates of the copepod Calanus finmarchicus at different locations across the North Atlantic between May 1998 and June 2004. Animals were incubated for 2-9 days and fed either with natural food assemblages or with cultured algae. During this period, we measured both somatic weight-specific growth rates (measured as protein change) and aminoacyl-tRNA synthetases (AARS) activity. We found a highly significant relationship between AARS activity and growth in protein content (R2 = 0.55, P < 0.001). Significant AARS activity also occurred when growth was negative, the relationship predicting an AARS activity level of ≤8.33 nmPPi·mg protein -1·h-1 when somatic growth is zero. This is because AARS activity is expected even when growth is negative, owing to the continued protein turnover in the cells. The AARS method allowed for the first time the study of protein metabolism in overwintering C. finmarchicus. Our study results showed that overwintering copepods had significantly lower values of AARS activity than non-diapausing animals (t = -3.51, P < 0.002). The AARS method opens the possibility to better understand physiology dynamics of deep-water organisms (e.g. the beginning and end of diapause). © The Author 2006. Published by Oxford University Press. All rights reserved. This work was supported by grants from the University of Las Palmas de Gran Canaria (Spain) and the Spanish Ministry of Education, Culture and Sport (MECD, EX-2002-0456) that allowed L. Y. to visit the Marine Biology Station in Espeland (Norway) and the Institute Maurice LaMontagne in Mont-Joli (Canada). [.] Completion of this work was funded by the European Social Fund (I3P programme, CSIC). This work is a contribution to the PML Core Strategic Research Programme and to the Marine Productivity UKGLOBEC Programme (NERC, NE/C508418/1) Peer Reviewed